Knowledge, Attitudes, and Practices Related to Hypertension among Adult People in Selected Areas of Uttara, Dhaka, Bangladesh. (East West Medical College Journal, 2025)
Background: Hypertension often called a “silent killer”, is a leading cause of cardiovascular diseases globally. This study focuses on the knowledge, attitude and practices (KAP) related to hypertension among adults in Uttara, Dhaka. Understanding the KAP of hypertension is essential to developing effective health interventions and promoting preventive measures to reduce hypertension-related morbidity and mortality in this area.Methods: This descriptive cross-sectional study was conducted among 170 respondents selected by using simple random sampling method   from areas of Dhaka North City and Dhaka South City Corporation. Relevant data were collected through face-to-face interview with the help of semi-structured questionnaire.Results: Among the total 170 respondents from different locations in Uttara, Dhaka, with 31.8% being male and 68.2% female. Regarding association between socio-demographic characteristics and various KAP aspects related to hypertension. Age (18-35 years) and education (Bachelor's) were significantly associated with better knowledge, positive attitudes, and healthier practices regarding hypertension. Profession (service holders) and income (10000-20000 BDT) were also significantly linked to knowledge and practices. Regarding knowledge among the respondents while 78% of participants had good knowledge of hypertension and 93% display positive attitudes towards its prevention, only 38% engage in effective practices for prevention of condition.Conclusion: This study offers valuable insights into the knowledge, attitudes, and practices (KAP) regarding hypertension among adult people in Uttara, Dhaka. Although attitudes toward hypertension prevention were generally positive, the findings suggest that individuals lack sufficient guidance and motivation to implement and sustain health behaviours about hypertension prevention and control.EWMCJ Vol. 13, No. 2, July 2025: 125-130